An investigation into the problems of estimating activity durations in projects - Wyrozębski, Paweł; Ścierski, Piotr (Badanie problemów i rozwiązań szacowania czasu trwania działań w projektach, 2020)
The article presents a theoretical and empirical investigation into the problems of estimating activity durations in projects. Uncertainty, the uniqueness of projects as well as their complexity make the process of estimation particularly difficult, but still crucial for successful project planning and implementation. As part of the literature analysis, the main techniques for project tasks estimating were presented. Classification was carried out and possible ways of their use were shown. The purpose of the research was to explore the actual use of the estimation methods and practices, to analyze their effectiveness and to identify obstacles in the process of activity time estimation. A survey was conducted on 40 project management specialists. The group of respondents was diverse in terms of company size, type and profile of implemented projects, importance of projects for the organization’s activities, as well as knowledge and experience in project management
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 2, s. 181-198
Keywords: project management; project; project time management; estimation techniques; project planning; zarządzanie projektami; projekt; zarządzanie czasem projektu; techniki szacowania; planowanie projektu